A Dual-Task Paradigm Using the Oral Trail Making Test While Walking to Study Cognitive-Motor Interactions in Older Adults - Langeard, Antoine; Torre, Marta Maria; Temprado, Jean-Jacques (Frontiers in Aging Neuroscience, 2021)
Introduction. With aging, gait becomes more dependent on executive functions, especially on switching abilities. Therefore, cognitive-motor dual-tasks (DT) paradigms should study the interferences between gait and switching tasks. This study aimed to test a DT paradigm based on a validated cognitive switching task, in order to determine whether it could distinguish older-old adults from younger-old adults. Methods. Sixty-five healthy older participants divided into 29 younger-old (<70 years) and 36 older-old (≥ 70 years) were evaluated in three single tasks conditions: a cognitive task including a processing speed component (Oral-Trail Making Test part-A [OTMT-A]), a cognitive task including a switching component (Oral-Trail Making Test part-B [OTMT-B]) and a gait evaluation at normal speed. They were also evaluated under two dual-tasks conditions, one associating gait with OTMT-A and the other associating gait with OTMT-B. Cognitive and gait performances were measured. Comparison of cognitive and gait performances between condition, logistic regression, and Receiver Operating Characteristic analyses were performed. Results. Cognitive and gait performances were differently affected by the different conditions (single-task, dual-task, OTMT-A, OTMT-B). The OTMT-B produced higher interference on gait and cognitive performances. Moreover, a higher number of errors on the OTMT-B performed while walking was associated with the older-old age group. Conclusion. Using validated cognitive flexibility tasks, this DT paradigm confirms the high interference between switching tasks and gait in older age. It is easily implemented, and its sensitivity to age may highlight its possible usefulness to detect cognitive or motor declines.